Employment effects of a payroll-tax cut: Evidence from a regional tax exemption experiment - Ossi Korkeamäki; Roope Uusitalo (Institute for Labour Market Policy Evaluation (IFAU), 2006)
In this paper we evaluate the effects of a regional experiment that reduced payroll-taxes by 3–6 percentage points for three years in Northern Finland. We match each firm in the target region with a similar firm in the control region and estimate the effect of the payroll-tax reduction by comparing employment and wage changes within the matched pairs before and after the start of the experiment. According to our results the reduction in the payroll-taxes led to somewhat faster wage growth in the target region. The increase in wages offset roughly half of the impact of the payroll tax cut on the labour costs. The remaining labour cost reduction had no significant effects on employment.
Keywords: J18; J23; J38; J58; J65; J68; 330; Payroll-tax; Labour demand; Tax incidence; Propensity score matching; Lohnsummensteuer; Arbeitsnachfrage; Schätzung; Finnland